An Observational Study to Assess Outcome of NSTEMI Patients with Raised Serum Uric Acid Level in a Tertiary Care Hospital of Bangladesh - PJ, Chakma; M, Barua; SA, Kuryshi; B, Barua; MS, Roy (Journal of Cardiovascular Medicine and Cardiology, 2020)
Background: Non-ST Segment Elevation Myocardial Infarction (NSTEMI) is the commonest form of ACS and a leading global cause of premature morbidity and mortality. Evidences link serum uric acid with short and long-term major adverse outcomes (MACE) in patients with NSTEMI. Objective: To see in-hospital outcome of NSTEMI patients with raised serum uric acid level. Methodology: This cross-sectional observational study was conducted in the Department of Cardiology, Sylhet MAG Osmani Medical College Hospital, Sylhet during the period from July, 2017 to June, 2019. Fifty NSTEMI patients with raised serum uric acid (>7mg/dl in male; >6mg/dl in female) level (Group A) and fifty NSTEMI patients with normal serum uric acid level (group B) admitted within 24 hours of symptom onset were consequently enrolled. In-hospital complications and mortality were recorded while continuing standard treatment for the event. Results: The mean age was 60.82 (SD 9.62) years in group A and 49.90 (SD 10.40) years in group B. The mean age of the patients of group A was significantly higher than patients of Group B (p<0.001). Male preponderance was in both groups (84.0% versus 80.0%; p=0.603). Diabetes mellitus (52.0% versus 22.0%; p=0.002), hypertension (78.0% versus 52.0%; p=0.039) and dyslipidaemia (48.0% versus 12.0%; p<0.001) were more frequent in group A than that of group B. But smoking status (70.0% versus 66.0%; p=0.668), family history of CAD (10.0% versus 26.0%; p=0.476) did not differ significantly. Killip class did not differ significantly between group A and group B (p=0.127). In-hospital mortality was 5 (10.0%) patients in group A and 2 (4.0%) patients in group B; did not reach the level of significance (p>0.05) and complications such as post MI angina, cardiogenic shock, acute left ventricular failure, re-infarction, sinus tachycardia, sinus bradycardia, atrial flutter, atrial fibrillation, bundle branch block, ventricular tachycardia, ventricular fibrillation did not differ significantly between the two groups (p>0.05). Conclusion: There is no significant difference between in-hospital outcome (mortality and complications) of NSTEMI patients with raised and normal serum uric acid level.